Solid Phase Synthesis of Cadaverine on Polymer Support - Santhakumari, V. (Asian Journal of Chemistry, 2012)
Cadaverine is a naturally occurring polyamine which is closely associated with spermine and spermidine, two major polyamines which regulate growth processes in living beings. Using polystyrene as solid support and with the help of a photocleavable linker, cadaverine was synthesised. The only purification process involved throughout the synthesis is filtration and washing with suitable solvents. Cadaverine was first synthesised over polystyrene support and then cleaved from matrix photolytically. The yield and purity of the sample was studied using differently cross linked polystyrene resin with divinyl benzene as the cross linking agent. The effect of one photocleavable linker was studied. The synthesis of linker was done by classical organic synthetic procedure.